The balance between clashing visual and idiothetic cues during path integration with redirected walking - Lavy, Guy; Maidenbaum, Shachar (Frontiers in Virtual Reality, 2026)
IntroductionAs we walk we perceive our motion by external channels such as vision, and by internal ones such as the vestibular and proprioceptive senses. But what happens when these channels offer contradicting information? Previous work has shown that by manipulating visual gain during movement the user’s path can be redirected, a procedure known as redirected walking. While the behavioral dominance of visual cues on the immediate path has been well demonstrated, potential residual effects of the internal senses on path integration have not been well quantified - will it disrupt participant’s answer in the visual reference frame or even bias it towards the correct answer by the internal cues reference frame as part of a weighted integration process? Or will vision dominate to the point where it suppresses the other clashing inputs? Furthermore, it is unclear to what extent such effects might be consistent within and across individuals.MethodsHere, we use the classic triangle completion task combined with redirected walking to quantify this balance and test for accuracy in the visual reference frame vs. the idiothetic reference frame.ResultsWe find that as expected vision dominates participants' conscious perception, that accuracy within the idiothetic reference frame is low on average compared to the control of performing the tasks without redirection, and that it is modulated by the level of redirected gain in a way which is generally stable within individuals. However, we also find significant individual differences across participants with some even having an opposite strong and stable bias towards the idiothetic reference frame.DiscussionThese findings offer insight into the basic science of human navigation and multisensory integration, and hold implications for practical applications in virtual environment design and locomotion with redirected walking. Specifically, VR developers and researchers should keep in mind that just because a user’s path is being properly redirected, it does not mean that their real-world physical path does not leave traces in their internal representations of space and may potentially have residual effects on their spatial memory in the individual participant level.